ULAMA AND VISION 2030: SAUDI ARABIA GOVERNMENT'S STRATEGIES TO NAVIGATE A SUCCESSFUL ECONOMIC REFORM - Ulya, Nashiha; Basyar, Hamdan (UI Scholars Hub, 2026)
Saudi Arabia's Vision 2030 seeks to diversify its oil-dependent economy, but scepticism persists due to past reform failures, particularly in fiscal policy and labour markets. Ulama, as key figures in the Saudi